Utilizing Speed Reading Technique for Students’ Ability in Comprehending Text - Asdar, Asdar; Hamsiah, A.; Angreani, A. Vivit; Lutfin, Nursamsilis; M, Asia; bin Tuan Kechik, Tuan Nordin (AT-TA'LIM, 2022)
Learning to read in junior high school is one of the language skills that plays an important role. Reading skill is the third skill that is mastered by students in having a role in language skills and mastery of other subject matter. This study aims to determine students' speed-reading ability. This research used descriptive quantitative method. The population of this study were all students of class VIII SMP Negeri 35 Makassar with a total of 288 students. The sample is 36 students. The sampling technique is a side random technique. Data obtained were analyzed using the percentage technique. The results of the data analysis showed that from 36 students as respondents, only 20 students (55.55%) managed to score above 75. This shows that the speed-reading ability of class VIII students of SMP Negeri 35 Makassar is still poor because it is still under of the standard, which is at least 85% of all respondents. Therefore, it is recommended that students and teachers be more active and that the learning support facilities are improved.